Mindfulness and compassion for youth with psychotic symptoms: A description of a group program and a consumer's experience. Issue 4 (2nd October 2019) - Hickey, Tara; Pen Name, Emily; Nelson, Barnaby; Meadows, Graham
ABSTRACT: An 8-week mindfulness and compassion program was developed for youth at risk for, or already experiencing, psychosis, based on UK national guidelines for developing interventions. The aim of this paper is to provide a program description and first hand account of a participant's experience. First, mindfulness skills are taught. Next an emotional regulation model is introduced, to help participants understand how psychotic experiences, anxiety and depression contribute to a heightened threat system, and how compassion can help them. The program contains meditations (e.g. breath practice, compassionate friend) and practices for use in daily life (e.g. STOP practice). The second author found mindfulness allowed her to feel and acknowledge her experience and give her emotions the recognition they needed. Being self-compassionate was a new concept, which at times was challenging but helped her realize her emotions were normal and she could manage difficult emotions using soothing practices. Furthermore, being part of a group helped her realize she was not alone. Mindfulness and compassion skills can be helpful for youth with psychotic experiences. A group program can provide a safe place to share experiences and reduce isolation. An evaluation of the program will be the focus of future papers.